PROGRAM DESA BUKU TAMAN KYAI LANGGENG MAGELANG SEBAGAI SOLUSI MENUMBUHKAN BUDAYA BACA MASYARAKAT - Dani, Desy Ery (Faculty of Humanities, Diponegoro University, 2012)
Through the Books Village Program, the government of Magelang city is trying to implement a new alternative innovation in nurturing reading culture to society, targeting Kyai Langgeng Park visitors. It is an attempt to solve the chronic problem of lack of reading interest and library visit among the citizens. Gathering data was through interview, observation, and bibliography study, resulting in some conclusions that to further succeed this program, the government needs more commitment and strengthened cooperation between government, intellectual institution, and society to prepare and support book reading culture. Â Keywords: desa buku, library, reading habit